Boosting the terahertz absorption spectroscopy based on the stretchable metasurface. Issue 1 (9th December 2022) - Yan, Dexian; Feng, Qinyin; Yang, Ji; Li, Xiangjun; Zhang, Le; Zhao, Yang; Li, Jining
Abstract : A method to enhance the terahertz absorption spectrum is realized by dynamically stretching the Au-coated PDMS metamaterial. Abstract : Terahertz (THz) absorption spectroscopy is widely used for molecular label-free fingerprinting detection, but it is not capable of efficiently analyzing trace-amount sample materials. For improving the efficiency of terahertz absorptance spectroscopy detection, we propose a sensing strategy by treating the geometry sweeping spoof surface plasmon polariton (SSP) of the stretchable metasurface. For the first time, the geometry sweeping can be realized by dynamically stretching the polydimethylsiloxane (PDMS) flexible substrate, leading to the resonant frequency variation of the unit cell. This design provides a significant absorption enhancement factor about 270 times for a 0.1 μm lactose film in a broad terahertz band, enabling the unambiguous identification of different trace-amount samples. The designed method exhibits a novel solution for the enhancement of broad-band terahertz absorption spectroscopy and great application potential in the field of detecting trace-amount samples.